2019
DOI: 10.1093/ehjcvp/pvz045
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacogenomic polygenic response score predicts ischaemic events and cardiovascular mortality in clopidogrel-treated patients

Abstract: Aims  Clopidogrel is prescribed for the prevention of atherothrombotic events. While investigations have identified genetic determinants of inter-individual variability in on-treatment platelet inhibition (e.g. CYP2C19*2), evidence that these variants have clinical utility to predict major adverse cardiovascular events (CVEs) remains controversial. Methods and results  We assessed the impact of 31 candidate gene polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 33 publications
1
95
0
Order By: Relevance
“…Lead investigators were invited to share DNA samples, platelet reactivity test results, patient characteristics, and cardiovascular outcomes to perform candidate gene and GWAS. 22 To date, 17 sites from 13 countries have joined the ICPC, contributing data representing 8,829 clopidogrel-exposed patients. Of those patients, a DNA sample was available in 5,119 patients, a DNA sample and platelet reactivity data in 4,511 patients, and in 2,844 patients a DNA sample, platelet reactivity data, and clinical outcome data were available.…”
Section: Methodsmentioning
confidence: 99%
“…Lead investigators were invited to share DNA samples, platelet reactivity test results, patient characteristics, and cardiovascular outcomes to perform candidate gene and GWAS. 22 To date, 17 sites from 13 countries have joined the ICPC, contributing data representing 8,829 clopidogrel-exposed patients. Of those patients, a DNA sample was available in 5,119 patients, a DNA sample and platelet reactivity data in 4,511 patients, and in 2,844 patients a DNA sample, platelet reactivity data, and clinical outcome data were available.…”
Section: Methodsmentioning
confidence: 99%
“…These data were further supported by a study of 760 cardiovascular patients treated with clopidogrel; it found that the CYP2C19*2 genotype accounted for only 5.2% of the platelet reactivity phenotype [31]. The genetic background of this variability is indeed probably multigenic, as shown by a recent collaborative study [32].…”
Section: The Early Evidence For Platelet Function Testingmentioning
confidence: 66%
“…It has several key advantages over PFTs, including quickly available, unequivocal results using current point-of-care assays, the absence of inter-individual variability, and, most importantly, there being no need to potentially challenge the patient with an antiplatelet drug for several days before a PFT. However, and as mentioned above, the currently available knowledge of the genetic background governing antiplatelet drug pharmacodynamics only explains between 3.5% and 12% of clopidogrel response [29][30][31][32], and the present genetic panel available poorly reflects the drug's pharmacodynamics. Nevertheless, several trials have investigated the clinical impact of a strategy based on genetics to tailor antiplatelet drug treatment in de-escalation settings.…”
Section: Genetic Tests or Platelet Function Tests?mentioning
confidence: 99%
“…Furthermore, we should detect the concentration of clopidogrel and its active metabolite to assess CYP2B6 activity. Since several polymorphisms impacted the clinical outcomes of clopidogrel therapy in the present study, a strategy utilizing a pharmacogenomic polygenic response score is needed to predict cardiovascular events in the future [44].…”
Section: Discussionmentioning
confidence: 99%